Decolonizing the sodomite : queer tropes of sexuality in colonial Andean culture - Horswell, Michael J. (Michael Jenkins), 1965- (University of Texas Press, 2005)
This is a study of alternative gender and sexuality in the colonial Andean world, which uses the concept of the third gender to reconsider some key aspects of Andean culture and provides an alternative history and interpretation of the much-maligned aboriginal subjects the Spanish referred to as 'sodomites.'